Model of Internalization of Honest Character Education and Student’s Discipline in Improving the Quality of Elementary Schools - Astari, Sharli Yunita; Putra, Alhadi Yan; Rahman, Andi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The objectives of this research are to be able to describe the internalization of strengthening honest character education, describe the internalization of strengthening disciplined character education, and explain the supporting factors and inhibiting factors in the internalization of strengthening honest and disciplined character education in improving the quality of SD 115 Palembang. This research was conducted at SD 115 Palembang. This research uses descriptive research with a qualitative approach. Data collection was carried out using observation, interviews, and documentation. Based on the research results above, it can be concluded that Internal analysis of educational and disciplinary character is essential for effective teaching, ensuring students understand and comply with all teaching methods, including disciplinary approaches. This study aims to analyze the role of teacher personality and discipline in enhancing student performance in SD Negeri 115 Palembang. It focuses on three main aspects: transformation of teacher personality and discipline to students, interaction between teachers and students, and transformation of teacher personality and discipline in learning and school environment. The research uses a four-step process model: inquiry, question, repeat, and action. The inquiry involves teachers guiding students in their school environment, the question consists of understanding students to develop teacher personality and discipline, the repetition in the research suggests the effectiveness of teaching character through teacher personality and discipline, and the action is learning from school to school. The results of internalizing the honest and disciplined character values of students in learning and the school environment have a positive impact where students develop honest and disciplined characters starting from morals, character, and attitudes within the students so that students always obey Allah SWT and His Messenger.